Yield Performance of Intercropped Marantha arundinacea L. (Arrowroot) in Two Rubber Plantation Designs - Jianxiong Huang; Jian Pan; Yuanxu Wei; Tianzhan Dong; Xiaoyan Zhang; Hanqi Tu; Xiuquan Wang (Agronomy, 2023)
Developing rubber agroforestry systems is crucial to ensure the sustainable development of natural rubber cultivation. This study focuses on the starch crop Maranta arundinacea (arrowroot) and assesses its productivity and influencing factors when intercropped in 6–7-year-old conventional single-row and double-row rubber plantations. We analyze various aspects, including light resources, root distribution, soil nutrients, arrowroot growth characteristics, and product quality. The results indicate that the daily average photosynthetically active radiation (PAR) in the double-row rubber agroforestry system intercropping area ranges from 896.4 to 940.2 μmol·m−2·s−1. Additionally, the rubber tree roots near the intercropping area are less dense (107.0 g cm−3). In contrast, the conventional single-row rubber agroforestry system has a significantly lower daily average PAR of only 145.7 μmol·m−2·s−1, and the nearby rubber tree roots are more abundant (616.2 g cm−3). Although soil nutrient levels were slightly lower in the intercropping area on the double-row treatment compared to the single-row treatment, there was no statistical difference (p < 0.05). Arrowroot’s photosynthetic capacity in the double-row rubber agroforestry system intercropping area is significantly greater than in the single-row rubber agroforestry system intercropping area. The yield per unit area in the former (23.46–27.47 t·ha−1) is also significantly higher than in the latter (2.87–4.75 t·ha−1, p < 0.05), with higher starch content. Therefore, arrowroot exhibits higher productivity when intercropped in double-row rubber agroforestry systems, making it suitable for establishing a “rubber–arrowroot” agroforestry model to enhance the yield per unit area of rubber plantations.